2008
DOI: 10.1309/ajcpvmdqu2zjdpbl
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Mortality Associated With Prompt Gram Staining of Blood Cultures

Abstract: Gram stains of positive blood cultures are the most important factor influencing appropriate therapy. The sooner appropriate therapy is initiated, the better. Therefore, it is reasonable to expect that the sooner Gram stains are performed, the better. To determine the value of timely Gram stains and whether improvement in Gram stain turnaround time (TAT) is feasible, we compared data for matched pairs of patients with cultures processed promptly (<1 hour TAT) with data for patients with cultures not processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 14 publications
1
85
0
4
Order By: Relevance
“…Previous studies have shown that timeliness of detecting bloodstream pathogens improves antimicrobial therapy, reduces costs, and decreases length of stay and patient mortality. [3][4][5][6][7][9][10][11] Timeliness and accuracy of preliminary blood culture results represent 2 important, evidence-based quality indicators that are closely linked to clinical outcomes.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that timeliness of detecting bloodstream pathogens improves antimicrobial therapy, reduces costs, and decreases length of stay and patient mortality. [3][4][5][6][7][9][10][11] Timeliness and accuracy of preliminary blood culture results represent 2 important, evidence-based quality indicators that are closely linked to clinical outcomes.…”
Section: Commentmentioning
confidence: 99%
“…Faster results reporting has been shown to be associated with lower mortality, 3 especially when combined with clinical consultation. 4,5 Other benefits of rapid reporting include improved selection of antimicrobial therapy, [6][7][8][9] lower overall health care costs, 10 and reduced length of stay.…”
mentioning
confidence: 99%
“…These infection rates continue to uptrend, posing a substantial public health risk by driving providers to utilize broad-spectrum antimicrobials and potentiating the cycle that creates MDROs (1)(2)(3). To minimize these threats, early administration of appropriate antimicrobial therapy is critical, as are antimicrobial streamlining to optimal therapy and discontinuation of inappropriate therapy, particularly in the setting of contaminated cultures (4)(5)(6)(7). Utilizing time-consuming conventional methods of organism identification can delay the time to optimal therapy (TTOT) and increase patient exposure to unnecessary antimicrobials.…”
mentioning
confidence: 99%
“…En nuestro hospital, siguiendo las recomendaciones del Clinical and Laboratory Standards Institute, el tiempo fi jado para avisar la tinción de Gram de un hemocultivo identifi cado como positivo es de 1 hora. Trabajos recientes han demostrado que el aviso dentro de este lapso está asociado a una disminución de la mortalidad de los pacientes 18 . En el año 2011, a diferencia de los años anteriores, nuestro laboratorio logró estar por sobre la meta, con la implementación de un cronómetro para el tecnólogo médico, que comienza a medir el tiempo desde que el equipo de hemocultivos avisa la positividad del frasco.…”
Section: Artículo Originalunclassified